Ekonomi Politik Media Dalam Pemberitaan Kasus Korupsi - Edon, Yunilia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACTEvery mass media is a form of idiology, which is then embraced by journalists in the mass media, andused in the mass media. The purpose of this research is to find out the uniqueness of the law embraced by theJavanese magazine, and to determine whether or not something is wrong in the memory. The approach in thisresearch is paradigm with critical discourse analysis approach (AWK). The source of this study is four texts onnews about the law in the May 2018 edition of the Journal of Justice. While the research data is in the form ofphrases, vocabulary, or sentences analyzed with the following steps: transcribing data from documents (newstext), grouping/ Classifying words, phrases, or words, and background images of key words raised in a contextcontaining legal ideology, draw conclusions. Data processing techniques using documentation techniques. Theresults of this study indicate that in legal cases contains legal ideology that is more pro-people and justice, anddoes not produce strength in the news. Sharpness, criticality of managers in issues in their reporting is only aform of reporting that has no affiliation to the government. The manager's ideology can be seen from the way ofchoosing words, phrases, sentences, and quotations that give rise to participation in the news, and evidence ofcirculars which are proven to be crimes made and used in the news.